Evaluasi Flowering Time Bunga Anggrek (Koleksi Kebun Raya Purwodadi) - Nina Dwi Yulia (JURNAL PENELITIAN BIOLOGI BERKALA PENELITIAN HAYATI, 2009)
The orchid collection of Purwodadi Botanic Garden is one of unique and attractive collection. The exotica of orchid flower were appeared from compacting of shape, color and size flower. The orchids have a different of flowering period of orchid flowering. This observation aimed to do data flowering time of orchid collection Purwodadi Botanic Garden which be done during 2007–2008. The data of evaluation include orchid species which flowering, flowering time and be complicated which open up of flower duration. The Paphiopedilum glaucophyllum is one of orchid which have flowering time long of years. The flowering time of orchid species could be found in July.